The impact of alloplast and allograft on bone homeostasis: Orthodontic tooth movement into regenerated bone. Issue 8 (10th March 2020) - Klein, Yehuda; Kunthawong, Natthapong; Fleissig, Omer; Casap, Nardi; Polak, David; Chaushu, Stella
Abstract: Background: The aim of the study is to examine bone healing following augmentation with allograft or β‐tricalcium phosphate (β‐TCP) and evaluate orthodontic tooth movement (OTM) into the augmented sites. Methods: The study included two parts. Part I included the alveolar bone regeneration model. Osseous defects were created by extraction of the maxillary first molars in C57BL/6 mice, and the sockets were filled with allograft, β‐TCP, or left unfilled (n = 6/group). Mouse allograft was prepared by a novel method using long bones. Maxillae were collected at 2, 4, and 6 weeks for microcomputed tomography (μCT) and histological analysis. In Part II, OTM was performed after full bone healing, through grafted and unfilled sockets (n = 10/group), and the second molar shift was assessed using μCT. Results: Bone volume and trabeculation were reduced in β‐TCP compared with allograft and non‐grafted groups at 2 and 4 weeks post‐grafting, but similar at 6 weeks. Graft particles could be detected at 2 weeks post‐grafting for β‐TCP, and at 2 and 4 weeks for allograft. Increased osteoclasts' presence was observed in the β‐TCP group at 2 and 4 weeks compared with allograft and control. OTM was similar in the two graft groups, but impaired versus the non‐grafted controls. Conclusion: β‐TCP and allograft induce full normal healing but alter OTM into the regenerated sites.